Cutaneous histoplasmosis: An unusual presentation with nasal obstruction - Surabhi Sinha; Diksha Agrawal; Kabir Sardana; Purnima Malhotra (Wolters Kluwer Medknow Publications, 2020)
Histoplasmosis is a systemic fungal disease that may be presented with a variety of clinical manifestations, usually as an opportunistic infection in immunocompromised individuals. We present an HIV seropositive patient with a large fleshy growth causing left-sided nasal obstruction, as an unusual presentation. The lesions shrunk dramatically and almost completely on intravenous amphotericin-B lipid complex (ABLC) given for 2 weeks followed by long-term oral itraconazole.